(untitled) (Journal of Cancer Research Updates, 2022)
Cancer accounts for nearly one-quarter of deaths in the United States. The life expectancy after standard treatment for these patients is dismal. New treatment modalities should be considered and evaluated. Ascorbic Acid (AA, Vitamin C) is a relatively low cost and safe nutrient even when given at very high doses (intravenous) that could be a very relevant co-adjuvant in cancer treatment. In vitro and in vivo studies have shown benefit of using high dose intravenous vitamin C as adjuvant therapy in cancer patients. There is significant supporting evidence of the benefits of the use vitamin C with chemotherapy.